What Limits the Rate Capability of Li-S Batteries during Discharge: Charge Transfer or Mass Transfer? - Zhang,T; Marinescu,M; Walus,S; Kovacik,P; Offer,GJ (Journal of the Electrochemical Society, 2017)
Li-S batteries exhibit poor rate capability under lean electrolyte conditions required for achieving high practical energy densities. In this contribution, we argue that the rate capability of commercially-viable Li-S batteries is mainly limited by mass transfer rather than charge transfer during discharge. We first present experimental evidence showing that the charge-transfer resistance of Li-S batteries and hence the cathode surface covered by Li2S are proportional to the state-of-charge (SoC) and not to the current, directly contradicting previous theories. We further demonstrate that the observed Li-S behaviors for different discharge rates are qualitatively captured by a zero-dimensional Li-S model with transport-limited reaction currents. This is the first Li-S model to also reproduce the characteristic overshoot in voltage at the beginning of charge, suggesting its cause is the increase in charge transfer resistance brought by Li2S precipitation.